Validation of the AJCC 8th prognostic system for breast cancer in an Asian healthcare setting. (August 2018) - Wong, R.X.; Wong, F.Y.; Lim, John; Lian, W.X.; Yap, Y.S.
Abstract: Aims: We aim to validate the AJCC 8th edition prognostic staging system for breast cancer in an Asian setting. Methods: Clinico-pathologic information and cancer-specific survival (CSS) outcomes of 6287 stage I to III patients with invasive breast cancer who underwent upfront surgery at SingHealth institutions in Singapore from 2006 to 2014 were analyzed. Survival distributions for the different staging systems were estimated by the Kaplan-Meier method and compared using the log-rank tests. Multivariable Cox proportional hazards models were used, with Akaike Information Criterion (AIC) and Harrell's Concordance Index (C-index) to compare both staging systems. Among patients with positive hormone-receptor status, 84.8% received endocrine therapy. Among the cohort, 60.3% of received chemotherapy; 82.1% of node positive patients received chemotherapy and 86.0% of HER2-enriched patients in whom chemotherapy was also indicated received adjuvant HER2-targeted therapy. Ninety-seven percent of patients received anthracyclines and/or taxanes containing chemotherapy regime. Results: The median follow up was 64 months. 2921 patients (46.5%) were discordant between the anatomic and prognostic systems of which 363 (5.8%) were upstaged and 2558 (40.7%) were down-staged. For all patients, stages in both the prognostic and anatomic systems were discriminating for 5-year CSS. Controlling for age, ethnicity and receipt of chemotherapy, the prognostic staging system model (AIC = 7538.87, C = 0.79) presented slightly better explanation and concordance of survival times than the anatomic staging system model (AIC = 7607.31, C = 0.77). Conclusion: The prognostic staging system was better than the anatomic staging system in predicting outcomes but the anatomic system remains relevant due to its ease of use. Highlights: AJCC 8 th prognostic staging system was implemented on 1 st Jan 2018. Our study of >6000 patients from 2006 shows a suggestion that the prognostic staging system provides better concordance. Most of our patients had standard of care; 2 nd /3 rd gen chemo, trastuzumab and endocrine therapy if indicated. More work should be done on the incorporation of gene expression assays. Anatomic staging system remains relevant for ease of use.